A Battery for Arctic Radio Repeater Systems. - Armstrong,William A; Barnes,William D (1979)
The effect of temperature on the working voltage of air depolarized cells (Model 608z, 2000 Ah) at various stages of discharge has been investigated. Discharge currents of 0.2 to 1.0 A at temperatures from 20 C to -55 C were examined as were the effects of increasing the electrolyte concentration from 22% to 27% and 29% KOH. The results confirm that air depolarized cells can form a suitable power source for an unattended 30 W radio repeater station in the arctic if the cells are connected in a series/parallel arrangement such that the current drain from each cell does not greatly exceed 0.2 A. (Author) Abstract in French.